2000
DOI: 10.1038/sj.sc.3101035
|View full text |Cite
|
Sign up to set email alerts
|

Psychological wellbeing among carers of people with spinal cord injury: a preliminary investigation from South India

Abstract: Study design: A cross-sectional study that assessed people with spinal cord injury (SCI) and their carers who attended the 3-day health care program. Objectives: The study examined the nature and prevalence of the factors associated with psychological morbidity among carers of people with SCI. Setting: A community reintegrated population of persons with SCI and their carers attended the 3-day program in the Department of Physical Medicine and Rehabilitation, Christian Medical College Hospitals, Vellore, South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…2,21 This study did not find any significant relationship between the level of injury and the caregiver burden, and is similar to the findings reported in other nonWestern countries. 7,22 This could be because of the fact that the majority of the paraplegic persons, who were expected to be independent in self-care and mobility, suffered from moderate-to-severe disability requiring assistance in many ADL. Information obtained during the interview revealed a lack of appropriate mobility equipment and adaptive devices, inappropriate home environment, restricting wheelchair access and poor socioeconomic status of many families as factors affecting caregiving roles.…”
Section: Discussionmentioning
confidence: 99%
“…2,21 This study did not find any significant relationship between the level of injury and the caregiver burden, and is similar to the findings reported in other nonWestern countries. 7,22 This could be because of the fact that the majority of the paraplegic persons, who were expected to be independent in self-care and mobility, suffered from moderate-to-severe disability requiring assistance in many ADL. Information obtained during the interview revealed a lack of appropriate mobility equipment and adaptive devices, inappropriate home environment, restricting wheelchair access and poor socioeconomic status of many families as factors affecting caregiving roles.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters, such as carers' stress and their quality if life might also be included. [31][32][33][34] Conclusions and implications…”
Section: Level Of Injurymentioning
confidence: 99%
“…13 Several studies have shown negative effects of giving support on the quality of life of the caregivers of persons with SCI. 11,[14][15][16][17][18][19] Weitzenkamp et al studied stress and depression in 124 spouses of persons with SCI that had been injured more than 23 years ago. Spouses who were caregivers reported higher levels of stress, burnout, fatigue, resentment and depression compared to spouses who were not caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Unalan et al, 16 for example, found no correlation between the seriousness of the SCI and complications and caregivers' quality of life, whereas Schulz et al 20 reported that the amounts of assistance provided for the persons with SCI were strongly correlated with depression of caregivers. Further, most studies used small sample sizes 14,16,18 or used mixed samples of partners, other family members, nonfamily members or professional caregivers. 5,10,13,14,16 As a result, the burden of support as perceived by partners of persons with SCI still needs clarification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation